Kepatuhan Kepala Daerah dalam Melaksanakan Putusan Pengadilan Tata Usaha Negara Padang yang Telah Berkekuatan Hukum Tetap - Fegi Fegi; Khairani Khairani; Hengki Andora (UNES Law Review, 2023)
Based on Article 67 letter b of Law Number 23 of 2014 concerning Regional Government, it is explained that the Regional Head as a State Administrative Officer has an obligation to comply with all provisions of the Legislative Law including Decisions issued by the State Administrative Court. In Decision Number 11/G/2020/PTUN.PDG Regarding Dismissal of Wali Nagari Kinari by the Regent of Solok and Decision Number 23/G/2018/PTUN.PDG Concerning Dismissal of the West Pasaman Regional Secretary by the West Pasaman Regent there are forms of non-compliance committed by the Head Regions as State Administrative Officials, among others, do not revoke disputed TUN Decrees, do not revoke and do not issue new TUN Decrees. The absence of the application of strict sanctions and the low level of awareness of the TUN officials concerned are factors in the non-implementation of PTUN decisions that have permanent legal force by the Regional Head. The Administrative Court's procedural law has regulated sanctions against TUN bodies/officials who do not comply with PTUN decisions, but these arrangements are not concrete because they still depend on implementing regulations which have not been realized until now, this condition provides an opportunity for officials to disobey PTUN decisions because there is no things to worry about if you don't comply. This situation is one of the factors for weak law enforcement in Indonesia.